Eﬀect of interval training and electromagnetic ﬁeld therapy on functional balance and peripheral arterial disease severity in patients with diabetic polyneuropathy: randomised controlled trial - Abdelaal, Ashraf Abdelaal Mohamed; Albatati, Roz Saeed; Yamani, Danyah Mohammed; Abdullatif Ali, Reem Amin; Salem, Ghaidaa Adel; Mahboob, Lamis Hatem; Alotaibi, Dhay Talal; Alqurashi, Maha Fawzi (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. To evaluate the cross-over association of moderate-to-high-intensity interval-training (M-HIIT) and low-frequency pulsed-electromagnetic ﬁeld therapy (LFPMT) on functional balance (FB) and ankle-brachial index (ABI) in patients with diabetic polyneuropathy (DPN).Methods. Twenty-four participants with DPN, age 40–65 years, 0.6 < ABI 0.9, were randomly allocated into group A (n = 7) and received M-HIIT followed by LFPMT, group B (n = 9) and received LFPMT followed by M-HIIT, or group C (n = 8) as the control group. Each of the LFPMT (15 Hz, 20 G, for 24 min) and the M-HIIT was provided twice weekly, for 4 weeks. Variables were evaluated pre and after 4 and 8 weeks.Results. After 4 weeks, the FB signiﬁcantly increased [by 9.08% (p = 0.00) and by 6.82% (p = 0.00)] and the ABI signiﬁcantly increased [by 7.84% (p = 0.01) and 12.57% (p = 0.03)], while after 8 weeks, the FB signiﬁcantly increased [by 13.03% (p = 0.00) and 11.26% (p = 00)] and the ABI signiﬁcantly increased [by 10.05% (p = 0.01) and 13.01% (p = 0.01)] in groups A and B, respec-tively. Signiﬁcant diﬀerences existed between-groups after 4 weeks in the [FB (p = 0.00) and ABI (p = 0.02)], and after 8 weeks [FB (p = 0.00) and ABI (p = 0.01)]. Post-hoc comparisons revealed the FB most signiﬁcantly increased (p = 0.001) in group A, while the ABI more signiﬁcantly increased (p = 0.02) in group B.Conclusions. Combined M-HIIT and LFPMT programs were eﬀective in improving FB and ABI. Furthermore, starting the re-habilitation regimen with M-HIIT followed by LFPMT had a superior eﬀect in improving the FB while starting the program with LFPMT followed by M-HIIT was more eﬀective in improving the ABI in patients with DPN.
Keywords: exercise therapy; magnetic ﬁeld; falling; ankle brachial index; diabetic polyneuropathy